2022
DOI: 10.1007/s11604-022-01335-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on percutaneous radiofrequency and microwave ablation for liver metastases over the last decade

Abstract: Purpose This review aimed to summarize the treatment outcomes of percutaneous radiofrequency ablation (RFA) and microwave ablation (MWA) for metastatic liver tumors based on the findings of published studies over the last decade. Materials and methods Literature describing the survival outcomes of ablation therapy for liver metastases was explored using the PubMed database on April 26, 2022, and articles published in 2012 or later were selected. The includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…However, we cannot deny the fact that for some experienced and aggressive centers, the curative surgery has been attempted to be applied in a small portion of patients with liver metastasis, especially among those with CTMLD. With the development of intraoperative ultrasound technique and the prevalence of RFA, partial hepatectomy combined with intraoperative ultrasound‐guided RFA has been extensively applied in various primary or secondary metastatic liver malignancies 12–15 . Our final results indicated that although GBC patients with CTMLD seemed to be operable, significantly worse OS and DFS were detected even patients were actively treated.…”
Section: Discussionmentioning
confidence: 79%
“…However, we cannot deny the fact that for some experienced and aggressive centers, the curative surgery has been attempted to be applied in a small portion of patients with liver metastasis, especially among those with CTMLD. With the development of intraoperative ultrasound technique and the prevalence of RFA, partial hepatectomy combined with intraoperative ultrasound‐guided RFA has been extensively applied in various primary or secondary metastatic liver malignancies 12–15 . Our final results indicated that although GBC patients with CTMLD seemed to be operable, significantly worse OS and DFS were detected even patients were actively treated.…”
Section: Discussionmentioning
confidence: 79%
“…For example, a combination of microwave ablation with Camrelizumab (PD-1 inhibitor) in the setting of lung cancer achieved an overall response rate in one-third of the patients, while the disease control rate was achieved in approximately two-thirds [56]. Microwave ablation has also been studied in the setting of metastatic disease [57 ▪ ]. More studies are needed, particularly in the area of EUS-guided microwave ablation for pancreatic lesions.…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Unlike surgery or radiation therapy, which can be invasive and carry signi cant side effects, MWA uses microwave energy for targeted tumor cell elimination. This approach not only achieves effective local ablation but also reduces the side effects often seen with conventional treatments [9,10,11,12]. MWA's minimally invasive nature and its ability to preserve healthy liver tissue make it particularly advantageous for patients who might not be suitable for more aggressive treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the Child-Pugh classi cation has emerged as a crucial framework for guiding treatment strategies in patients with malignant liver tumors. While there has been a gradual increase in research on percutaneous microwave ablation for malignant liver tumors in recent years, the majority of studies have been limited in scale and struggle to offer robust guidance for clinical practice [9,10,11]. Furthermore, the current research ndings remain inconclusive regarding the in uencing factors of microwave ablation therapy, such as Child-Pugh classi cation, lesion size, and the number of lesions.…”
Section: Introductionmentioning
confidence: 99%